Historyzm wobec starożytności w dziełach J.J. Winckelmanna, W. von Humboldta i F. Schlegla. Próba rekonstrukcji i zarys polskiej recepcji - Junkiert, Maciej (Slavia Occidentalis, 2013)
The second half of the XVIIIth century contributed to a radical change in the cultural relationship with the past. Historicism, understood as the widespread method of conceptualization of human inventions, appeared not only in historiography, but also marked its presence in literature, philosophy, architecture and art. The aim of this article is to explore some of the outlooks on the connection between historicism and classical antiquity in the works of Winckelmann, Humboldt and Schlegel, important German thinkers with a significant impact on Polish literature and culture.